Palbociclib plus endocrine therapy in older women with HR+/HER2– advanced breast cancer: a pooled analysis of randomised PALOMA clinical studies. (September 2018) - Rugo, Hope S.; Turner, Nicholas C.; Finn, Richard S.; Joy, Anil A.; Verma, Sunil; Harbeck, Nadia; Masuda, Norikazu; Im, Seock-Ah; Huang, Xin; Kim, Sindy; Sun, Wan; Iyer, Shrividya; et al.
Abstract: Aim: Because incidence of breast cancer and comorbidities increase with age, it is important to determine treatment benefit in elderly patients. We evaluated outcomes with palbociclib plus endocrine therapy in patients aged ≥65 years. Methods: Data were pooled from three randomised studies (NCT00721409, NCT01740427 and NCT01942135) of women with HR+/HER2− advanced breast cancer (ABC). In PALOMA-1 (open-label) and PALOMA-2 (double-blind, placebo-controlled), treatment-naïve patients received palbociclib plus letrozole or letrozole alone. In PALOMA-3 (double-blind, placebo-controlled), patients with endocrine-resistant disease received palbociclib plus fulvestrant or fulvestrant alone. Results: Among 528 patients treated with palbociclib plus letrozole and 347 treated with palbociclib plus fulvestrant, 218 (41.3%) and 86 (24.8%), respectively, were aged ≥65 years. Versus endocrine therapy alone, median progression-free survival was significantly improved in patients aged 65–74 years (hazard ratio [HR], 0.66; 95% confidence interval [CI], 0.45–0.97; P = 0.016) and ≥75 years (HR, 0.31; 95% CI, 0.16–0.61; P <0.001) receiving palbociclib plus letrozole and in patients aged 65–74 years (HR, 0.27; 95% CI, 0.16–0.48; P <0.001) receiving palbociclib plus fulvestrant; few patients aged ≥75 years received palbociclib plus fulvestrant (HR, 0.59; 95% CI, 0.19–1.8; P = 0.18). Patient-reported functioning and quality of life was maintained. No clinically relevant differences in palbociclib exposure were observed between age groups. Although myelosuppression was more common among patients aged ≥75 years, incidence of grade ≥III myelosuppression was similar across age groups, and febrile neutropenia was uncommon (≤2.4%); no new safety concerns were identified in older patients. Conclusions: Palbociclib plus endocrine therapy is an effective, well-tolerated treatment for older patients with ABC. Highlights: We studied palbociclib plus endocrine therapy (ET) for older HR+/HER2– advanced breast cancer (ABC) patients. Palbociclib improved progression-free survival in older patients irrespective of prior treatment status. Patient-reported quality of life was maintained. Palbociclib plus ET has a favourable safety profile in older patients. Palbociclib plus ET is an effective treatment option for older ABC patients.